2023
DOI: 10.3390/life13030780
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Culture—A Sustainable Approach to Explore Plant Stresses

Abstract: Plants are constantly faced with biotic or abiotic stress, which affects their growth and development. Yield reduction due to biotic and abiotic stresses on economically important crop species causes substantial economic loss at a global level. Breeding for stress tolerance to create elite and superior genotypes has been a common practice for many decades, and plant tissue culture can be an efficient and cost-effective method. Tissue culture is a valuable tool to develop stress tolerance, screen stress toleran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 128 publications
0
4
0
Order By: Relevance
“…International Service for Agri-biotech Acquisition Applications reported that the potential achievements in agriculture depend on biotechnology (Utomo et al, 2017). Wijerathna-Yapa and Hiti-Bandaralage (2023) demonstrated that tissue culture and recombinant DNA are technologies utilized to improve crops' agronomic traits, resistance to unfavourable environmental factors and enhanced nutritional values. However, risks and ethical problems associated with the practices of biotechnology in agriculture have led to the limitation of its usage (Montgomery, 2015).…”
Section: Background Of the Studymentioning
confidence: 99%
“…International Service for Agri-biotech Acquisition Applications reported that the potential achievements in agriculture depend on biotechnology (Utomo et al, 2017). Wijerathna-Yapa and Hiti-Bandaralage (2023) demonstrated that tissue culture and recombinant DNA are technologies utilized to improve crops' agronomic traits, resistance to unfavourable environmental factors and enhanced nutritional values. However, risks and ethical problems associated with the practices of biotechnology in agriculture have led to the limitation of its usage (Montgomery, 2015).…”
Section: Background Of the Studymentioning
confidence: 99%
“…17,18 The utilization of tissue culture techniques for quantifying stress tolerance of various crops has been increasing rapidly. [19][20][21] Polyethylene glycol (PEG), a non-toxic water-soluble polymer which is neither metabolized nor absorbed by cells, is available in a wide range of molecular weights (e.g., PEG-4000, PEG-4500, PEG-6000, PEG-8000, and PEG-10000). 22 It induces water deficit in in vitro tissue cultures in a manner similar to that observed in vivo in cells of intact plants subject to drought conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Morpho‐physiological responses of young cacao hybrids to different water deficit stress conditions showed significant differences under control conditions 17,18 . The utilization of tissue culture techniques for quantifying stress tolerance of various crops has been increasing rapidly 19–21 . Polyethylene glycol (PEG), a non‐toxic water‐soluble polymer which is neither metabolized nor absorbed by cells, is available in a wide range of molecular weights (e.g., PEG‐4000, PEG‐4500, PEG‐6000, PEG‐8000, and PEG‐10000) 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Plant tissue culture is generally used for plant propagation under aseptic conditions. This technique is now widely applied in different fields because it can be used under time and space constraints [ 16 ]. Plant tissue culture is employed for large-scale production of new whole plants or specific plant parts.…”
Section: Introductionmentioning
confidence: 99%